The Relationship between Laboratory Biomarkers and Nutritional Interventions in Emergency Nursing Care - Raed Najem Alotaibi; Abdulmajeed Mohammed Albogami; Homoud Salah Aljeri; Majed Assaf Alsabee; Ahmed Saleh Alfayez; Abdullah Zaid Alsufayyan; Khalid Mohammed Asiri; Abeer Habbab Alotaibi; Talal Salem Alzahrani (International Journal of Medical Toxicology and Legal Medicine, 2024)
This review has summarized the relationship between laboratory biomarkers and nutritional interventions in emergency nursing care and underlined how important these factors are in patient outcomes. Laboratory biomarkers are, therefore, crucial in providing insight into the physiological status of patients and guiding appropriate nutritional strategies. Nutritional interventions are thus important strategies in mitigating malnutrition and improving recovery in critically ill patients through the use of enteral and parenteral feeding. This review focuses on biomarkers' interaction with nutrition, highlighting how they can further contribute to precision care in the emergency room. By integrating the evidence of recent research, the study outlines the importance of a multidisciplinary approach in managing critically ill patients in order to optimize outcomes and reduce complications.